Church and State development in the Eastern Caucasus in the second half of the 19th century (based on the sermons of archpriest Nikolai Kotlyarevsky) - Abidat Gazieva (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
The study of confessional issues in the Eastern Caucasus, using the example of the activities of Archpriest N.V. Kotlyarevsky, the study is devoted to, it examines the issues of moral development of the Orthodox population of the Eastern Caucasus, the ideological role of clergy in matters of family and marriage, and public service. The Orthodox clergy in the Caucasus was an integral part, the base for the implementation of the Caucasian policy in the region. The integration component of the Caucasian policy has become a priority, especially in the period from the 1930s. XIX century, when as a result of acculturation processes there was a change in management vectors - from the military-political subordination of the region to its development, by means of involvement in the trade, economic, cultural field of the empire, and the formation of a socio-cultural space. Acculturation processes, both state and domestic, came to the forefront of state policy in the region. The paper highlights the issues of the place and role of the Orthodox clergy in the spread of education in the region, charitable activities, especially in the second half of the 19th century, which was due to the influx of the empire's resettlement policy into the region. The Orthodox clergy of the Caucasus became the conductor of the state acculturation of the region, supervising the issues of matrimonial ties, the revival of Orthodoxy, its spread in the region, the value orientations of family and marriage, as well as state initiatives and practices in the Eastern Caucasus.